Natural polymers composed mucoadhesive interpenetrating buoyant hydrogel beads of capecitabine: Development, characterization and in vivo scintigraphy - Upadhyay M.; Vardhan H.; Mishra B. (My University, 2025)
The present research deals with the optimization and preparation of aluminium ion cross-linked buoyant interpenetrating polymeric network (IPN) microbeads (MBs) of locust bean gum (LBG) and sodium alginate (NaAlg) carrying Capecitabine (CAP). The formulation was prepared by ionotropic gelation method. The optimization was done by Response Surface Methodology based Box Behnken Design (BBD) involving a significant changes or effect on responses, particle size, drug entrapment and buoyancy on varying the concentration of polymeric blend (LBG:NaAlg), cross-linker (Aluminum chloride; AlCl3) and pore former (sodium bicarbonate; NaHCO3). Finally, the best optimized batch of buoyant IPN MBs of CAP obtained through BBD was examined through different evaluations that exhibited particle size of 402.12 ± 1.9 μm, drug entrapment 82.45 ± 2.5% and % buoyancy 85.03 ± 1.1% with total floating time of greater than 10 h. The formed IPN MBs showed good buoyancy in gastric pH and better mucoadhesion in intestinal pH. The results of pharmacokinetic study displayed improved systemic circulation, bioavailability and extended plasma half-life of encapsulated CAP within polymeric shell than free CAP. To ensure the gastroretention of formed buoyant IPN MBs, the gamma scintigraphy study performed revealed the gastroretention of MBs for more than 6 h suggesting the designed and developed optimized batch is effective for gastroretention with improved bioavailability. © 2019 Elsevier B.V.